Transmission characteristics of blue-green vortex beams in the lower atmosphere-upper ocean link. (August 2022) - Wang, Mingjun; Cheng, Qun; Li, Jianqing; Wang, Yuhang
Highlights: Establish the transmission model of the blue-green vortex beam in the atmosphere, air-sea interface, and ocean at different incident angles. Analyzed the changes of atmospheric turbulence of different intensities, the influence of sea surface wind speed on the sea surface, and the changes of ocean turbulence of different intensities. The evolution behavior of blue-green vortex beams during the air-sea trans-medium transmission under different turbulence intensities, different wind speeds, and different transmission distances are analyzed. The work will provide a theoretical basis for the blue-green vortex beam to complete the air-sea cross-media optical transmission and optical communication experimental research. Abstract: The research on the air-sea cross-media transmission characteristics of blue-green vortex beam will help to realize the wireless optical link communication of space-air-ground-sea in the future. This paper presents a transmission model of a blue-green vortex beam through the atmosphere turbulence, air-sea interface, and ocean turbulence. The evolution behavior of Laguerre-Gaussian beams transmitted from the atmosphere to the ocean at different incident angles is analyzed, and the transmission characteristics of the beam's air-sea cross-media transmission under different turbulence intensities, different wind speeds, and different transmission distances. The results show that when the turbulence intensity is stronger, the sea surface wind speed is greater, or the transmission distance is longer, causing Laguerre-Gaussian beam intensity fluctuations to increase, and the dark core at the center of the beam gradually disappears. The phase distortion becomes more serious, and the final complete distortion. Compared with the vertical transmission of the vortex beam with the incident angle of 0°, when the vortex beam is transmitted obliquely with the incident angle of 45°, the Laguerre-Gaussian beam intensity will be weakened and the phase distortion will increase. Our work will provide a theoretical basis for the blue-green vortex beam to complete the air-sea cross-media optical transmission and optical communication experimental research.